Unimas’s achievements in the implementation of the first phase of the national higher education strategic plan (psptn) 2007-2010. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2013)

(untitled)
The National Higher Education Strategic Plan (PSPTN) is an initiative from the Ministry of Higher Education (MoHE), to develop the quality of human capital and to make Malaysia a hub of excellence in higher education regionally and internationally (Ministry of Higher Education, 2007). In August 27, 2007 PSPTN was launched by the then Prime Minister, YAB Dato‘ Seri Abdullah Haji Ahmad Badawi. PSPTN outlined four phases of development: viz, Phase 1: Laying the Foundation in 2007-2010, followed by Phase 2: Strengthening and Enhancement (2011-2015), then Phase 3: Excellence (2016-2020) and finally Phase 4: Glory and Sustainability that should begin beyond the year 2020.